2012
DOI: 10.1074/jbc.m111.246785
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Karyopherin α1 and Nuclear Import by Mammalian Target of Rapamycin

Abstract: Background:The protein kinase mTOR can negatively regulate transcription factors and stress transcriptional responses. Results: mTOR and its associated phosphatase PP2A suppress the constitutive nuclear import of STAT1 and apoptosis via karyopherin-␣1. Conclusion: mTOR controls STAT1 activity and apoptosis by regulating STAT1 nuclear import. Impact: mTOR and karyopherin ␣1 constitute a molecular link between mitogen or nutrient sensing and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
(63 reference statements)
3
19
0
Order By: Relevance
“…Caspase-3 (CASP3) cleavage products were measured as a marker of apoptosis. As previously shown (20), cleaved CASP3 levels were reduced in STAT1-deficient U3A cells compared with those in 2fTGH controls (Fig. 4A, columns 5 versus 1); rapamycin significantly increased cleaved CASP3 levels in 2fTGH but not in U3A cells (Fig.…”
Section: Versus 3)supporting
confidence: 80%
See 1 more Smart Citation
“…Caspase-3 (CASP3) cleavage products were measured as a marker of apoptosis. As previously shown (20), cleaved CASP3 levels were reduced in STAT1-deficient U3A cells compared with those in 2fTGH controls (Fig. 4A, columns 5 versus 1); rapamycin significantly increased cleaved CASP3 levels in 2fTGH but not in U3A cells (Fig.…”
Section: Versus 3)supporting
confidence: 80%
“…When inactivated, mTORC1 associates with latent (i.e. unphosphorylated) STAT1 in a macromolecular complex (18), enhances its nuclear import (20), and augments the subsequent induction of STAT1-dependent apoptosis genes. Mechanisms of latent STAT1 signaling and its regulation of apoptosis genes are reviewed in Yang and Stark (42).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the rapamycin-induced KPNA2 decrease was abolished in the presence of the proteasome inhibitor MG132 (Figure 3B ), suggesting that the mTOR pathway modulated the proteasome-mediated KPNA2 degradation in NSCLC cells. Notably, previous studies have shown that KPNA1 (a STAT1 karyopherin) interacts with mTORC1 in a complex that includes STAT1 and the mTOR-associated phosphatase PP2Ac [ 29 ]. To investigate whether mTOR modulated KPNA2 degradation through a physical association with KPNA2, we determined the association between KPNA2 and phospho-mTOR/mTOR by an immunoprecipitation assay.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al () found that autophagy activity was markedly increased when glioma stem/progenitor cells (GSPCs) were induced to differentiate using fetal calf serum (FCS), and that rapamycin, the activator of autophagy, could promote their differentiation. The mTOR signaling pathway was involved the regulation of autophagy, and mTOR could turn into its activated form, phospho‐mTOR, which can respond directly to mTOR activity (Fielhaber et al, ). Our study demonstrated that the expression of p‐mTOR, p‐p70S6K, and p‐4E‐BP1 declined after induction compared, which indicates that mTOR activity decreased during the neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%